2012
DOI: 10.1080/0951192x.2011.620008
|View full text |Cite
|
Sign up to set email alerts
|

An ontology-based method for the development of a troubleshooting configuration system

Abstract: A troubleshooting configuration is a critical way to implement the specific paradigm by integrating a set of specific elements to satisfy both technical criteria and users' needs. With the objective of enabling efficient generation of automotive troubleshooting configuration by reusing configuration knowledge, an ontology-based approach to building troubleshooting configuration knowledge is presented in this study. The utilisation of ontologies as metadata descriptions of the information sources is a possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…This systematisation is mainly about the structure and reuse of knowledge using modelling-based techniques. Recently, some research work has been reported to use ontologies to create semantic-based applications within the aerospace sector (Dadzie et al 2008), government sector (Horrocks 2008) telecommunication sector (Davies, Fensel, and van Harmelen 2008), medical and pharmaceutical sector (Hawker 2010) manufacturing sector (Kitamura and Mizoguchi 2007;Lin et al 2010;Mizoguchi 2004;Sanya, Shehab, and Roy 2010) automotive sector (Liang 2012) and recently the PSS (product service system) sector (Doultsinou et al 2009;Shen, Wang, and Sun 2012). Despite these advances, there has been lack of KBE frameworks for developing ontology-based multidisciplinary KBE systems within the aerospace industry.…”
Section: Introductionmentioning
confidence: 99%
“…This systematisation is mainly about the structure and reuse of knowledge using modelling-based techniques. Recently, some research work has been reported to use ontologies to create semantic-based applications within the aerospace sector (Dadzie et al 2008), government sector (Horrocks 2008) telecommunication sector (Davies, Fensel, and van Harmelen 2008), medical and pharmaceutical sector (Hawker 2010) manufacturing sector (Kitamura and Mizoguchi 2007;Lin et al 2010;Mizoguchi 2004;Sanya, Shehab, and Roy 2010) automotive sector (Liang 2012) and recently the PSS (product service system) sector (Doultsinou et al 2009;Shen, Wang, and Sun 2012). Despite these advances, there has been lack of KBE frameworks for developing ontology-based multidisciplinary KBE systems within the aerospace industry.…”
Section: Introductionmentioning
confidence: 99%